REKONTRUKSI ATURAN TENTANG SENGKETA LINGKUNGAN HIDUP ATAS TANAH YANG TERKONTAMINASI MINYAK: Reconstruction Of The Rules On Environmental Disputes Over Oil-Contaminated Land - Suharja, Mohamad (Fakultas Hukum, Universitas Trisakti, 2024)
Whereas environmental disputes are suspected to occur in areas where there are mining activities, etc., so that the Government is appropriate and supervises the resolution of environmental disputes. Whereas the legal regulations for environmental settlement before the Claimants file an environmental lawsuit, based on the Ministerial Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.22/MENLHK/SETJEN/SET.1/3/2017 Concerning Procedures for Managing Complaints of Alleged Environmental Pollution and/Or Destruction and/Or Forest Destruction (